Teaching strategies that promote organization and Mastery of Content - Arnold, Craig (California : Canter and Associates, 1996)
This video is one of the four in a staff development series. This series is designed to help you expand your teaching repertoire to include a variety of strategies that develop the thinking and learning skills necessary for a lifetime of learning
Copy available in DVD format
Executive producer, Lee Canter, Marlene Canter ; editor, Jay Shelp
Narrator: Ron Snow
Featuring: Pat Wolfe
Keywords: Mastery learning; Teaching; Teaching strategies